Neuroimaging Insights into Autism Spectrum Disorder: Structural and Functional Brain - Mahie Patil; Nofel Iftikhar; Latha Ganti (Health Psychology Research)
Autism Spectrum Disorder (ASD) is a condition that affects social communication, behavior, and interests. This review analyzes recent brain imaging studies to understand the biological basis of ASD. Studies using structural magnetic resonance imaging (sMRI) show that people with ASD often have less gray matter in key brain areas like the amygdala and superior temporal sulcus. There are also concerns with white matter connections in the brain. Functional magnetic resonance imaging (fMRI)studies show reduced connectivity within critical brain networks and irregular activation patterns when processing social information. Intervention studies suggest that targeted training can improve brain function related to social skills. Postmortem research reveals cellular and synaptic changes, such as fewer Purkinje cells and altered neuron organization. These findings highlight the importance of studying the social brain network in ASD and suggest the need for more long-term, comprehensive studies. This review is intended to contribute to the development of advanced diagnostic tools and therapies that will ultimately enhance the quality of life for individuals with ASD.